Pelayanan Sayang Warga Dalam Upaya Meningkatkan Kepemilikan Dokumen Administrasi Kependudukan (Di Kelurahan Sidotopo Wetan) - Septiani, Indah Nur; Arundinasari, Indira (Universitas Gajah Putih, Indonesia, 2023)
Population Administration is a series of structuring and controlling activities in the issuance of population documents and data through population registration, civil registration, management of population administration information and utilization of the results for public services and the development of other sectors. But at this time there are still many people who do not understand how important written evidence is. Many people are reluctant to take care of their population administration. The Surabaya City Population and Civil Registration Service (Disdukcapil) through the MSIB Internship Student with the position of Population Administration Service Assistant will be deployed in all Kelurahans and Subdistricts in Surabaya City by running one of the Programs namely Community Care Services which will be held at Balai RW intensively. This service uses a type of participatory service, meaning not only by being a consultant, but also as active actors involved as executors using a participatory approach method. The author as one of the MSIB Internship participants is placed in the Sidotopo Wetan Village. The result of this Community Compassionate Service is an increase in the orderly ownership of population administration documents in the Sidotopo Wetan Village.Keywords: Community Service, Sidotopo Wetan Village